L’abbaye cistercienne du Val-Richer (Calvados) : prospections microtopographique et géophysique d’un monastère disparu - Jean-Baptiste Vincent (Archéologie Médiévale)
The Cistercian abbey of Val-Richer was established in the middle of the 12th century inside a small valley of the Pays d’Auge, in Normandy. Since the French Revolution, the many changes made to the site have almost made disappear more than six centuries of monastic activity. In addition, the textual and iconographic sources relating to the abbey are scarce and do not provide any details on the location and morphology of the conventual buildings (even for the abbey’s church). It was then that we implemented different prospecting methods to understand the management of the environment and the spatial organization and to clarify the layout of this abbey which seems to have vanished. Topographic surveys were necessary to study the development of the environment (earthworks, the hydraulic network ...) in a particular hydro-geomorphological context (installed on a promontory). Moreover, thanks to a reasoned analysis of the electrical anomalies, it is possible to offer reconstituted versions while striving to expose the limits and the dangers of over-interpreting.